Commercial symptom monitoring devices in Parkinson’s disease: benefits, limitations, and trends - Daniel Rodríguez-Martín; Carlos Pérez-López; Carlos Pérez-López (Frontiers in Neurology)
Parkinson’s disease (PD) is a neurodegenerative disorder that significantly impacts patients’ quality of life. Managing PD requires accurate assessment of motor and non-motor symptoms, often complicated by the subjectivity in symptom reporting and the limited availability of neurologists. To address these challenges, commercial wearable devices have emerged to continuously monitor PD symptoms outside the clinical setting. The main devices include PKG™, Kinesia 360™, Kinesia U™, PDMonitor™, and STAT-ON™. These devices utilize advanced technologies such as accelerometers, gyroscopes, and specific algorithms to provide objective data on motor symptoms like tremors, dyskinesia, and bradykinesia. Despite their potential, the adoption of these devices is limited due to concerns about their accuracy, complexity of use, and lack of independent validation. The correlation between these devices’ measurements and traditional clinical observations varies, and patient usability and adherence remain critical areas for improvement. To optimize their utility and improve patient outcomes, it is essential to conduct validation and usability studies with a sufficient number of patients, develop standardized protocols, and ensure integration with hospital information systems.